Thomas Hobbes’s Translation of ‘The Plague of Athens’ (Thuc. 2.47.2–54): A First Critical Edition - Hoekstra, Kinch; Iori, Luca (Histos, 2022)
The article provides a sample presentation of the critical edition in progress of Thomas Hobbes’s translation of Thucydides, Eight Bookes of the Peloponnesian Warre (London, 1629). The specimen of the edition is Thucydides’ narration of the ‘Plague of Athens’, accompanied by an introduction that sets Hobbes’s edition in its historical context, considers his method of translation, and lays out some distinctive requirements for editing an early modern text. A note on the text explains the format and the editorial principles of the specimen.